Dungeon Siege II - Radcliffe, Doug (Wiley, 2005)
This is the exclusive, official guide to Dungeon Siege II, the sequel to Microsoft's best-selling role-playing game (RPG). Expected to be one of the biggest PC games this year, Dungeon Siege II promises the same hack-n-slash action with more involved character development options, a more fully developed story plus three times as many quests. Cover-to-cover, this guide is packed with comprehensive walkthroughs, detailed maps, in-depth strategies, and complete statistics straight from the game's designers. Its attractive, high-quality, full-color design will truly capture the spirit of the game.